Commitment Battles Gen Z Turnover: Fueled by Development and Satisfaction to Stay - Delvia Putri Aspasya; Ikram Yakin; Arman Jaya; Titik Rosnani; Hasanudin Hasanudin (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to provide growing body organizations develop effective retention strategies for Gen Z workers by identifying key drivers of turnover intentions in Indonesia. Methodology/approach: A quantitative approach was adopted, collecting data from 246 Gen Z employees via an online Google Forms questionnaire. Purposive sampling was used to target relevant respondents. Data were analyzed using SmartPLS 4 to assess the validity, significance, and explanatory power of both measurement and structural models. Results/findings: Employee commitment emerged as the strongest predictor of reduced turnover intention. Career development and job satisfaction positively influenced commitment, while job satisfaction also directly reduced turnover. The model explained 75.8% of the variance in turnover intention, demonstrating strong reliability and predictive power. Conclusions: Retention of Gen Z employees is driven by commitment fostered through career development, job satisfaction, fair treatment, meaningful work, and work-life balance highlighting the need for supportive, inclusive, and empowering work environments. Limitations: Findings are limited by the focus on Indonesian Gen Z employees, which may affect generalizability, and the cross-sectional design, which restricts causal inferences over time. Contribution: The study bridges theory and practice by confirming the mediating role of commitment in retention, offering HR professionals actionable strategies to retain Gen Z talent in developing economies.